Artificial Intelligence in e-Administration - Bierecki, Dominik; Karpiuk, Mirosław; Gaie, Christophe (PRAWO i WIĘŹ, 2025)
Nowadays, the influence exerted by artificial intelligence on many spheres of human life has been steadily on the rise. It is a tool that e-Administration can – or should – use in its activities. However, caution must be exercised when using artificial intelligence systems, as their inappropriate use can lead to several threats, including data leakage or infection of the ICT systems through which the public administration provides its services to society or other entities (including entrepreneurs). Artificial intelligence is both a challenge and a necessity for public administration. With the development of new technologies, it must use modern tools to meet society’s constantly evolving needs. Digitisation is now a widespread phenomenon, so meeting the needs of an information society forces public administration to look for new solutions, of which artificial intelligence is certainly one of these. The dogmatic-legal and theoretical-legal methods were employed to address the issues dealt with in the paper, which aims to analyse the need for e-Administration to use artificial intelligence. These methods have made it possible to review and analyse the applicable regulations and doctrinal views on the use of artificial intelligence systems by the public administration in the course of performing certain activities in cyberspace.